Vesicular Arbuscular Mycorrhizal Inoculation Influences Growth, Nutrient Absorption and Hyphae Colonization of Rough Lemon (Citrus limon) Seedlings - Chebet, D. K.; Wanzala, F. K.; Kariuki, W. (African Journal of Education,Science and Technology (AJEST), 2021)
Many researchers continue to illustrate the benefits of Vesicular Arbuscular Mycorrhiza fungi on crop output, particularly under unfavourable growth environment. In Sub Saharan Africa, mycorrhizae research on economically important fruit seedlings have attracted inadequate attention. The aim of this study was to determine the effect of Vesicular Arbuscular mycorrhiza fungi on the growth, nutrient absorption, and hyphal colonization of rough lemon (Citrus limon) seedlings grown in low phosphorus sand culture and low nutrient sand/soil planting media. The study showed that in non-inoculated plants increased in the corresponding P levels in sandy media as well as in the low sand/soil media in VAM inoculation with respect to lemon seedlings, the number of leaves and the area of the feed and thickness of the stem. The fresh and dry weights of roots, leaves and stems, and the leaf concentration of phosphorus, nitrogen and potassium were also increased by VAM inoculation. Inoculation also enhanced mycorrhizae hyphal colonization of roots and upraised the root absorptive surface area. This study demonstrates that VAM inoculation improves the competence of lemon seedlings to uptake and use scarce soil nutrients thereby enhancing seedling performance. Being a cheap and readily available technology, VAM incorporation is recommended in nursery propagation of seedlings to ensure a good start of clean and healthy fruit seedlings